Elements of criminal intent in crime Negative Comparative Study between Islamic Criminal Jurisprudence and Algerian Legislation - baali, djamel; aboukerkeb, abdelmadjid (Journal of Social Sciences and Humanities, 2021)
Criminal intent is one of the two forms of the moral element of a negative crime, as it expresses the true will of the perpetrator when he commits the crime, and it is of great importance in jurisprudence and the judiciary alike, and therefore no crime can be considered a complete negative unless the intention of the perpetrator from whom this criminal behavior was issued stemmed from From a bad and sinful intention, and this can only be proven with the availability of two elements: knowledge and will, through the existence of a psychological link between criminal activity and its consequences, and based on this matter, our study came as a comparison between Islamic jurisprudence and Algerian law.